Theory of microstructured polymer–electrolyte artificial muscles. (22nd June 2018) - Goodwin, Zachary A H; Eikerling, Michael; Löwen, Hartmut; Kornyshev, Alexei A
Abstract: Ionic electroactuator beams are promising systems for artificial muscles in microrobotics. Here a theory is developed to investigate one promising class of such systems, which employs flexible volume-filling electrodes impregnated with polymer–electrolyte. The theory provides analytical formulae for the equilibrium beam curvature as a function of voltage and structure-related operational parameters. It predicts a possible enhancement of beam curvature by orders of magnitude over that of flat electrodes. Volume-filling electrodes thus constitute one of the 'strongest' architectures for voltage-induced movement. Approximate expressions for the dynamics of tandem pore charging and beam deflection are developed to determine the maximum pore length that still warrants a sufficiently fast response time (up to 1 s). Upper bounds on applied voltage and response time constrain the maximal device thickness and curvature, and therefore, the resulting work such a device can perform.